Integration of nutrient, energy, light, and hormone signalling via TOR in plants. (2nd February 2019) - Wu, Yue; Shi, Lin; Li, Lei; Fu, Liwen; Liu, Yanlin; Xiong, Yan; Sheen, Jen
Abstract : This review summarizes and discusses recent findings on the complex roles of TOR in integrating nutrient, energy, light, and hormone signals to mediate meristem activation and plant growth and development. Abstract: The multidomain target of rapamycin (TOR) is an atypical serine/threonine protein kinase resembling phosphatidylinositol lipid kinases, but retains high sequence identity and serves a remarkably conserved role as a master signalling integrator in yeasts, plants, and humans. TOR dynamically orchestrates cell metabolism, biogenesis, organ growth, and development transitions in response to nutrient, energy, hormone, and environmental cues. Here we review recent findings on the versatile and complex roles of TOR in transcriptome reprogramming, seedling, root, and shoot growth, and root hair production activated by sugar and energy signalling. We explore how co-ordination of TOR-mediated light and hormone signalling is involved in root and shoot apical meristem activation, proliferation of leaf primordia, cotyledon/leaf greening, and hypocotyl elongation. We also discuss the emerging TOR functions in response to sulfur assimilation and metabolism and consider potential molecular links and positive feedback loops between TOR, sugar, energy, and other essential macronutrients.